Integrated Management Chilhood Illness (IMCI) in Primary Health Care: Literature Review - Totok Wahyudi; Endrat Kartiko Utomo; Fakhrudin Nasrul Sani; Susi Lastianingsih; Panji Azali; Diva Agustinaningrum (LPPM Universitas Duta Bangsa Surakarta, 2021)
Children death toll throughout the country in 2011 reaching 6.9 million, recorded 1900 deaths of children in a day and 800 deaths of children per hour. About 80% of deaths occur children in developing countries. The efforts of the World Health Organization (WHO) and the Ministry of health Indonesia (Health Department Indonesia) to lower mortality and pain globally is to introduce the Sick Child Initiative (SCI) or Integrated Management Of Childhood Illness (IMCI), namely the decision-making steps in managing childhood illness. In an attempt to increase the scope of discovery and enhances the life-threatening disease system on children, the Department of health has implemented an Integrated Management Childhood Illness (IMCI) in primary health care units. The study of this literature review to identify and explore the role of nurse practitioners so as to improve readiness in the integrated management childhood illness (IMCI). Literature search conducted by doing searches journals from both the international and national journals. Searches performed through two electronic data base i.e. PubMed and Google Scholar with the use of the key word are IMCI*, integrated management childhood illness, Primary Health care, MTBS*, puskesmas, management terpadu balita sakit. Respondents used in the journal obtained is a nurse, children and parents of children. There is no specific data that describes the role, competence, training and level of education owned integrated management method in nursing a toddler sick (IMCI, Of all the articles showed that the role of the nurse in the readiness of implementing integrated management childhood illness (IMCI) in primary health care is already quite active views of the IMCI followed training and work experience having before. Based on the above discussion of ten literature obtained that implementation of the IMCI at any primary health care in each country mainly in Indonesia still do not meet the standards in the granting of health services on a children sick